COVID-19 Dysautonomia - Goodman, Brent P.; Khoury, Julie A.; Blair, Janis E.; Grill, Marie F. (Frontiers in Neurology, 2021)
Objective: To report a case series of dysautonomia associated with COVID-19 infection. Methods: This is a retrospective review of patients evaluated in the autonomic clinic at our institution with suspected signs and symptoms of dysautonomia who underwent formal evaluation, including autonomic testing. Results: Six patients were identified with signs and symptoms suggestive of dysautonomia who underwent autonomic testing. All patients had symptoms typical of COVID-19 infection, though none were hospitalized for these or other symptoms. All patients reported symptoms of postural lightheadedness and near-syncope, fatigue, and activity intolerance. Five patients reported the onset of autonomic symptoms concomitant with other COVID-19 symptoms, with the other patient reporting symptom onset 6 weeks following initial COVID-19 symptoms. Autonomic testing demonstrated an excessive postural tachycardia in 4 patients, a hypertensive response with head-up tilt in 3 patients, orthostatic hypotension in 1 patient, and sudomotor impairment in 1 of the patients with excessive postural tachycardia. Conclusions: We present clinical features and results of autonomic testing in 6 patients with a history COVID-19 infection. While all patients reported typical features of orthostatic intolerance, fatigue, and activity intolerance, the results of autonomic testing were heterogenous, with orthostatic hypotension in 1 patient, excessive postural tachycardia typical of postural tachycardia syndrome in 4 patients, and postural hypertension in 3 patients.